2019
DOI: 10.3892/mmr.2019.9824
|View full text |Cite
|
Sign up to set email alerts
|

Galangin decreases p‑tau, Aβ42 and β‑secretase levels, and suppresses autophagy in okadaic acid‑induced PC12 cells via an Akt/GSK3β/mTOR signaling‑dependent mechanism

Abstract: Okadaic acid (OA)-induced neurotoxicity may be considered a novel tool used to study Alzheimer's disease (AD) pathology, and may be helpful in the development of a novel therapeutic approach. It has been reported that galangin inhibits β-site amyloid precursor protein-cleaving enzyme 1 expression, which is a key enzyme for amyloid β (Aβ) generation and is a potential drug candidate for AD therapy. However, further studies are required to confirm its neuroprotective effects in other AD models. The present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Therefore, we deduced that PK2 is responsible for improvements in oxidative stress and apoptosis in cardiomyocytes exposed to high glucose/high palmitic acid through stimulating PKR, but the underlying mechanism is still unknown. AKT has been shown to be involved in cardiovascular functions linked with cell survival, growth, proliferation, and angiogenesis by inactivating its downstream target GSK3β [44][45][46]. Dariushnejad et al [47] reported that the activation of the AKT signalling pathway in the hearts of high-fat diet-and streptozotocin-induced diabetic rats has a beneficial effect on apoptosis and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we deduced that PK2 is responsible for improvements in oxidative stress and apoptosis in cardiomyocytes exposed to high glucose/high palmitic acid through stimulating PKR, but the underlying mechanism is still unknown. AKT has been shown to be involved in cardiovascular functions linked with cell survival, growth, proliferation, and angiogenesis by inactivating its downstream target GSK3β [44][45][46]. Dariushnejad et al [47] reported that the activation of the AKT signalling pathway in the hearts of high-fat diet-and streptozotocin-induced diabetic rats has a beneficial effect on apoptosis and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…GSK3β has been shown to coimmunoprecipitate with Presenilin-1, which is a critical gene involved in the generation of Aβ and early onset AD [42] , [43] . In both the pathological and physiological state, active GSK3β has the ability to phosphorylate over 20 sites on Tau protein, leading to the formation of NFTs [44] , [45] . Several studies have shown that inhibition of GSK3β can induce the activation of Nrf2 under oxidative stress conditions in AD [46] , [47] , [48] .…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy can effectively clear the damaged/dead cells and long-lived protein aggregates, in normal neurons [132]. Autophagic regulation is comprised of two complicated signaling transduction pathways including the mTOR-dependent and mTOR-independent mechanisms, both of which are involved in the AD pathology [133,134]. Researchers have hypothesized that impaired autophagy significantly reduces the clearance of Aβ and tau deposition in the brain of AD patients and animal models [135].…”
Section: Other Mechanisms Mediated By Mams In Ad Pathogenesismentioning
confidence: 99%